PRE-STENTING IN A DIFFICULT URETER: WHAT IS THE INCIDENCE? Pre-Stenting in A Difficult Ureter - Khan, Haroon Sabir; Khan, Malik Nadeem Azam; Hanif, Faisal (Pakistan Armed Forces Medical Journal, 2018)
Objective: To estimate the occurrence of “difficult ureter” where stenting was performed as a preliminary step for passive ureteric dilatation before second ureterorenoscopy and to create awareness of the incidence of this abnormality in our setting. Study Design: Cross sectional prospective case review study. Place and Duration of Study: Study was conducted in Urology department of PNS Shifa Karachi, from Jul 2017 to Mar 2018. Material and Methods: All patients who presented to our institute for ureteric calculi with normal creatinine and no urosepsis were included in the study. The procedure was carried out either in spinal anesthesia or general anesthesia using laryngeal mask. The outcome data of ureterorenoscopyin all patients including those patients who required pre-stenting for difficult ureters were documented. Results: Ureterorenoscopy was performed in 164 patients (mean age 34 years, range 14 to 70 years) for treatment of ureteric calculi. Among these 29 patients (17.7%) had upper, 52 patients (31.7%) had middle and 83 patients (51%) had lower ureteric calculi. Stone clearance was achieved in 135 (82%) of patients. In 16 (9.7%) patients the stone had to be pushed back for Extracorporeal Shock Wave Lithotripsy later. “Difficult ureters” were encountered in 13 patients (7.9%) in which Double J stents were placed under fluoroscopy and staged successful ureterorenoscopy were performed after 2 to 3 weeks without any complication. Conclusion: There was a 7.9% (about 8%) incidence of encountering “difficult ureter” while performing ureterorenoscopy for ureteric calculi resulting in failed access for which a Double-J stent will have to be introduced to avoid ureteric injury. This possibility of occurrence of a “difficult ureter” and a staged ureterorenoscopy after 2 to 3 weeks should be discussed with the patients preoperatively, in order to avoid patient dissatisfaction after the procedure and allay his undue emotional suffering.